CHARACTERIZATION OF CHROMITE MINING WASTE VIA MINERALOGICAL AND GEOCHEMICAL APPROACHES, KHROMTAU SITE - Baltabayeva, Sara (School of Mining and Geosciences, 2023)
Chromite mining is known to generate substantial amounts of waste materials, which may contain potentially harmful minerals or elements that can impact the environment. In this study, mineralogical approaches were employed to characterize the chromite mining waste at the Khromtau site, which is one of the prominent chromite producers in Kazakhstan. The mineralogical characterization involved identifying and quantifying the minerals present in the waste materials using hand specimen and conventional optical microscopic techniques. The results of the study provided valuable information on the mineral composition of chromite mining waste, which can aid in environmental assessment, waste management strategies, resource recovery opportunities, and implementation of mitigation measures. The findings of this study contribute to the understanding of the environmental impacts associated with chromite mining waste and provide insights for sustainable waste management practices in the mining industry.
Keywords: Type of access: Restricted; Khromtau site; chromite mining waste